PENGARUH PROFITABILITAS, UKURAN DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP CASH HOLDINGS - Efrinal - (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This research was conducted to find out the effect of profitability, the size of the board of commissioners and institutional ownership of cash holdings in transportation and warehousing sector companies listed on the Indonesia Stock Exchange in 2017 - 2019. Research methods using secondary data are quantitative. The number of samples used as many as 37 samples from 48 companies were obtained using the purposive sampling method over a 3-year period that resulted in 111 observation results. The data in this study was processed using the Eviews 9 program with the panel data regression analysis method. The data analysis technique used based on the results of the research model test is a random effect model. The results of this study showed that profitability (ROE) and institutional ownership had a significant negative effect on cash holdings while the size of the board of commissioners had a significant positive effect on cash holdings. The ability of independent variables to explain dependent variables is 9.95%, while the remaining 90.05% is influenced by other variables outside the study model.